Thematic Objective Structured Clinical Examination (OSCE) of Medical Students - Lubna Meraj, Ayesha Rauf , Iffat Sultana , Rubina Naz, Ghulam Haider Khalid ,Bushra Khizar , Mobeen Iqbal (Journal of Rawalpindi Medical College, 2014)
Background : To study the students and faculty perception for incorporating long and short case in a ‘Thematic’ OSCE assessment of final year students. Methods: in this observational study 12 station with performance based OSCE for final year students, were developed. OSCE stations were divided in clusters of 3 stations. Each cluster started with a history from a real patient (non-standardized), followed by relevant physical examination on another real patient (standardized) and finally an interactive discussion on the two stations about diagnosis and management addressing clinical reasoning. Competency-based blueprint was determined after several discussions within the section of Medicine to ensure validity. Multiple trained examiners were used for grading purposes. Each station was given seven minutes. Feedback from students and faculty was obtained Results: Structured questionnaire was completed by 189 out of 200 students over two consecutive final year students’ batch. Thirty faculty members responded to the feedback questionnaire. More than 80% of students gave favorable feedback on various aspect of thematic OSCE. Faculty members also liked the new format for its efficiency, competency-based approach and real patients’ participation. Conclusion: Thematic OSCE can serve as a practical alternate for traditional assessment of undergraduate medical students in Pakistan.